Review of bubble and magnetically driven catalytic micro/nanomotors: Fabrication and characterization - Mirzazadeh Khomambazari, Soolmaz; Yusuf, Mohammad; Esmaeilkhanian, Amirhossein; Zarei, Raheleh; Hojjati, Mahsa; Sharifianjazi, Fariborz; Arabuli, Lili (Journal of Composites and Compounds, 2022)
Micro/nanomotors (MNMs) are very unique in performing tasks and performance according to their scale. These small and versatile motors are known as promising tools in various applications. The ultimate goal is the application of MNMs in various fields, which is considered an exciting technological challenge. Chemical fuel is reliable for the movement of MNMs. Among the various movement mechanisms that exist for these engines, bubble propulsion is one of the most important, and many engines have been investigated using this propulsion mechanism. Magnetic motors are another category of motors that move by applying a magnetic driving force and their direction of movement can be adjusted by the applied magnetic field. One of the most important challenges in the field of MNMs is the use of controlled and efficient engines, which requires the manufacturing and careful design of these engines. By incorporating of two engines, it is possible to benefit from the advantages of both, and at the same time, the limitations of each one are removed and the possibility of controlling the movement of the engine is provided. We will review the methods of manufacturing and characterizing MNMs which consume chemical fuel and move by bubble propulsion and also have magnetic properties and can propel by applying a magnetic field. These engines can reduce the common fuel used in chemical engines by applying magnetic driving force and switching their operation in response to changing conditions. Due to continuous innovations in this field, MNMs will profoundly impact the field of Nanorobotics.